2005
DOI: 10.1111/j.1440-1746.2005.03955.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase chain reaction based analysis of the cytotoxin associated gene pathogenicity island of Helicobacter pylori from saliva: An approach for rapid molecular genotyping in relation to disease status

Abstract: Background and Aims:The genetic composition of the intricate cytotoxin associated gene pathogenicity island (cag PAI) of Helicobacter pylori is known to significantly influence the outcome of the disease. Hence, analysis of complete cag PAI of H. pylori isolated from saliva would be of immense importance in standardizing saliva as a reliable non-invasive diagnostic specimen and also to evaluate the type of H. pylori infection. The aim of the present study was to analyze the genes of cag PAI of H. pylori for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
2
15
0
Order By: Relevance
“…Previous studies (Tiwari et al 2005, Loster et al 2006, Souto & Colombo 2008, Harris et al 2008) used PCR to diagnose an infection of H. pylori. These results are comparable to the results of the present study, in which there was a 95% success rate in the detection of H. pylori in the stomach.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies (Tiwari et al 2005, Loster et al 2006, Souto & Colombo 2008, Harris et al 2008) used PCR to diagnose an infection of H. pylori. These results are comparable to the results of the present study, in which there was a 95% success rate in the detection of H. pylori in the stomach.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southementioning
confidence: 99%
“…Li et al (1995) found 75% of saliva samples to be positive, which is similar to the results of Wang et al (2002), who found the bacterium in 71% of saliva samples. Tiwari et al (2005) studied 120 dyspeptic patients and detected H. pylori in the gastric and saliva samples from each patient. Both authors suggested that saliva may be a method of transmission and may potentially induce gastric reinfections, which supports the results of the present study.…”
Section: Detection Of H Pylori In Saliva and Dental Plaque By Southementioning
confidence: 99%
“…DNA isolation from salivary samples was performed according to phenol chloroform C-TAB method [8] . All the steps were performed in aseptic conditions to minimize contamination using cryocentrifuge (Eppendorf).…”
Section: Preparation Of Genomic Dna For Pcrmentioning
confidence: 99%
“…Cag A and cag T have been implicated to play an important role in the disease progression and can be used as biomarkers of virulent disease causing state of H. pylori [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation